Investigating nitrate uptake and transient storage in headwater streams among gradients of geomorphic complexity, land use, and restoration techniques - Mueller Price, Jennifer Suzanne, author; Bledsoe, Brian P., advisor; Gooseff, Michael Nikolai, committee member; Loftis, Jim C., committee member; Wohl, Ellen E., 1962-, committee member (Colorado State University. Libraries, 2010)
Headwater streams are a crucial component of nutrient processing in watersheds, owing to high surface-to-volume ratios that favor nitrate uptake and to the large percentage of headwater stream length in the total length of a river system. In this study, I explore how geomorphic characteristics may influence transient storage and nitrate uptake of streams across a gradient of land use and restoration practices. To examine linkages among geomorphic complexity, transient storage, and nitrate uptake in streams, I investigated an urban stream and two agricultural streams. Study reaches representing distinct geomorphic settings with varying substrate size, sinuosity, bed slope, and styles of restoration and management were chosen within each stream. I performed detailed physical characterizations and multiple nutrient injections of bromide and nitrate to estimate transient storage and nitrate uptake in each reach. Comprehensive data sets, including pebble counts, longitudinal profiles, cross-section surveys, hydraulic measurements, and benthic organic matter (fine and coarse), were collected to characterize physical complexity along each reach. To estimate parameters of transient storage and nitrate uptake, the OTIS model was run through UCODE for optimization of parameter estimates. Regression models were developed to relate attributes of flow and geomorphic complexity with transient storage and nitrate uptake parameters. The models showed associations among nitrate uptake velocity and length (vf, Sw) and transient storage parameters (Fmed200), which were influenced by key factors of geomorphic complexity (longitudinal roughness), flow (Reynolds number), and substrate condition (median grain size and fine benthic organic matter). There were no conclusive patterns showing that in-channel structures and natural revegetation of riparian areas promoted nitrate uptake in the study streams. For example, a reach with instream wood but without restoration structures exhibited more transient storage and comparable nitrate uptake when compared to a paired reach with extensive J-hook vane structures. Finally, an investigation of the urban stream before and after a high flow event indicated that transient storage and nitrate uptake are highly context-specific and mediated by interactions between geomorphic setting and flow variability.
Department Head: Luis A. Garcia.
Keywords: transient storage; nitrate uptake; Geomorphology -- Research; Watersheds -- Research; Stream restoration -- Research; Nitrates -- Research; Hyporheic zones -- Research